2016
DOI: 10.1016/j.jaac.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine and Parent Training for Children With Autism and Attention-Deficit/Hyperactivity Disorder: A 24-Week Extension Study

Abstract: Objective We previously reported a 2×2 randomized clinical trial of individual and combined treatment with atomoxetine (ATX) and parent training (PT) for attention-deficit/hyperactivity disorder (ADHD) symptoms and behavioral noncompliance in 128 children with autism spectrum disorder, ages 5–14 years. We now describe a 24-week extension of treatment responders and non-responders. Method One-hundred seventeen participants from the acute trial (91%) entered the extension; 84 of these were in two subgroups: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Initial responders continued to show sustained improvement in ADHD symptoms. Also, about a third of patients who were non‐responders to placebo responded to atomoxetine in the open label extension study period of 6 months [Smith et al, ]. This extension study aimed at the combined effect of Parent Training and Atomoxetine on Non‐compliant behavior of children with ASD and ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Initial responders continued to show sustained improvement in ADHD symptoms. Also, about a third of patients who were non‐responders to placebo responded to atomoxetine in the open label extension study period of 6 months [Smith et al, ]. This extension study aimed at the combined effect of Parent Training and Atomoxetine on Non‐compliant behavior of children with ASD and ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Atomoxetine, (both alone and combined with PT) significantly reduced ADHD symptoms (Handen et al, 2015). The authors conducted a 24-week extension study demonstrating that atomoxetine combined with PT was superior at reducing ADHD symptoms than atomoxetine alone (Smith et al, 2016). The effect sizes reported in the atomoxetine studies (0.59-0.98) are similar to the effect size reported for methylphenidate in children with ASD (0.67) (Research Units on Pediatric Psychopharmacology Autism Network, 2005), suggesting equivalent efficacy.…”
Section: Treatment Of Adhd and Hyperactivity Symptoms In Children Witmentioning
confidence: 99%
“…It has been reported that ATX or rTMS in combination with the behavior training had a better therapeutic effect when compared with the single method, but there are some reports showing no obvious advantage. 41,42 However, further in-depth research may need to increase sample size and optimize the treatment parameters.…”
Section: The Rtms Therapy Combined With Atx Administrationmentioning
confidence: 99%